Packaging Redesign of Zitrolin Film Coated Caplet 500 mg Production of PT Otto Pharmaceutical Industries to Increase Brand Awareness (The Indonesian Journal of Business Administration, 2021)
PT. Otto Pharmaceutical Industries in its production process produces more ethical medicines than OTC. The consideration is that the product is more widely used and in demand by the public. The ethical drug production process at PT Otto Pharmaceutical Industries must be made well, one of which is by making good and attractive product packaging. Product packaging design is a representation of the product. Good packaging is able to give a positive impression on the company's products and brands. With the growth of a positive image, it will be able to encourage the level of product sales (Anggoro, 2000: 59).The unit of analysis in this study is ethical drug packaging design and corporate image. This study seeks to see the extent to which ethical drug packaging designs can improve the company's image of PT. Otto Pharmaceutical Industries and in the end was able to increase sales of these ethical drug products.Quantitative methods are used in this study. Researchers collect data from several sources to achieve goals with appropriate and relevant information, namely primary and secondary data. Primary data was obtained by means of researchers preparing a questionnaire about the opinion of respondents about the packaging of Zitrolin Selaput 500 mg capsules. The respondents are doctors and marketing personnel. Secondary data was obtained by collecting information from the internet, literature and articles related to research. This study uses six criteria according to Keller (2013:171) as research indicators which include: Memmorability, Meaningfullness, Likalibility, Transfarability, Adaptability and Protectability.The results showed that the packaging design of Zitrolin Selaput 500 mg capsules was in the "Good" category. The "Good" category was able to maintain the position of Zitrolin Selaput 500 mg Caplet in the ethical drug market position for two years (2019 and 2020), but this condition cannot be tolerated because the market tends to be dynamic, the competition is getting tougher. The market position of Zitrolin Sealed Caplet 500 mg in 2019 and 2020 is below the top of mind by five brands, namely: Ziromax produced by PT Pfizer, Mezatin produced by PT Sanbe Farma, Zycin produced by PT Interbatt, Zithrax produced by PT Kalbe Farma and Zibramax produced by PT Guardians. The market position of Zitrolin Selaput 500 mg capsules needs to be improved, so that it does not continue to be below the top of mind of the five brands or even lose in the competition because the product brand is unknown or forgotten. Efforts to improve it need to be carried out in an optimal and planned manner towards the ""Very Good"" category. Keywords: Packaging, Brand, Design, Ethical, Zitrolin Film Coated Caplet 500 mg.